A48 DUODENAL ADENOCARCINOMA: A CASE REPORT. (1st March 2018) - Hansen, T; Manishen, W
Abstract: Background: Primary adenocarcinoma of the duodenum is implicated in less than 0.5% of all gastrointestinal cancers. Although rare, benign looking duodenal ulcers at time of endoscopy may represent more sinister pathology, particularly in the absence of H. pylori or NSAID use. Aims: We report a case of an elderly man with a benign appearing duodenal ulcer at endoscopy who ultimately developed metastatic carcinoma from a primary adenocarcinoma of the duodenum. Methods: Case report Results: A 72 year old male presented for a routine screening colonoscopy. At time of endoscopy, the patient gave a history of vague epigastric discomfort and melena stools over the past two days. He denied ASA or non-steroidal drug use and was a non-smoker. A gastroscopy and colonoscopy were pursued. Upon examination of the duodenal bulb, a small, benign appearing ulcer was noted on the anterior wall with no active bleeding. Antral biopsies for H.pylori were negative. No intestinal metaplasia was seen. He was prescribed proton pump inhibitor and instructed to seek follow up care with his family doctor. Approximately 8 months later, the patient began experiencing epigastric pain, nausea, early satiety and weight loss. He presented to the emergency room 11 months after the original endoscopy. A CT scan of the abdomen showed multiple hepatic metastases and lymphadenopathy at the porta-hepatis. A repeat gastroscopy revealed an ulcerated, stenotic mass at the pylorus, extending from the duodenal bulb. Biopsies of the pylorus revealed invasive adenocarcinoma, intestinal type. The patient was subsequently referred for palliative care. Conclusions: This case highlights that not all duodenal ulcers are benign. It may be worthwhile to ensure patients follow up with their endoscopist should they develop a recurrence of symptoms, at which time biopsy of the actual ulcer, if not healed, could be performed. Funding Agencies: None